2019
DOI: 10.1177/0885066619837939
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Putative Benefits of Tracheostomy Tube Placement in Patients on Extracorporeal Membrane Oxygenation: A Single-Center Experience

Abstract: Purpose: Patients supported with extracorporeal membrane oxygenation (ECMO) have been reported to have increased sedation requirements. Tracheostomies are performed in intensive care to facilitate longer term mechanical ventilation, reduce sedation, improve patient comfort, secretion clearance, and ability to speak and swallow. We aimed to investigate the safety of tracheostomy (TT) placement on ECMO, its impact on fluid intake, and the use of sedative, analgesic, and vasoactive drugs. Methods: Prospective dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
(43 reference statements)
0
17
0
Order By: Relevance
“…In noncoronavirus disease populations receiving extracorporeal membrane oxygenation, consideration of tracheostomy is recommended for patients deemed to be on a trajectory to recovery, as it has the same perceived benefits of reduced sedation requirements and a lower incidence of ventilatorassociated pneumonia. [22][23][24] In this study, patients receiving extracorporeal membrane oxygenation were selected for tracheostomy according to the same principles as nonextracorporeal membrane oxygenation patients. This pragmatic approach was taken given the current lack of literature surrounding extracorporeal membrane oxygenation in Covid-19 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In noncoronavirus disease populations receiving extracorporeal membrane oxygenation, consideration of tracheostomy is recommended for patients deemed to be on a trajectory to recovery, as it has the same perceived benefits of reduced sedation requirements and a lower incidence of ventilatorassociated pneumonia. [22][23][24] In this study, patients receiving extracorporeal membrane oxygenation were selected for tracheostomy according to the same principles as nonextracorporeal membrane oxygenation patients. This pragmatic approach was taken given the current lack of literature surrounding extracorporeal membrane oxygenation in Covid-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sixty-five patients (86.7 per cent) had been liberated from invasive mechanical ventilation, with a median (interquartile range) post-tracheostomy duration of ventilation of 12 (7-16) days. Moreover, 59 (86.7 per cent) of patients had been successfully decannulated and 44 (68.7 per cent) had been successfully discharged from hospital in a median (interquartile range) duration of 19 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) days and 32 (25-39) days, respectively.…”
Section: Outcomes and Mortalitymentioning
confidence: 99%
“…However, recent retrospective studies reported that tracheostomy can be safely performed in selected ECMO patients in whom benefits outweigh the risks, without an associated increase of transfusions and with a consequent reduction in analgesic, inotropic, and vasopressor usage. 61,62 Larger prospective studies need to confirm these promising results. Finally, we consider ECMO weaning, which may be either before or after weaning from mechanical ventilation, depending on the preference and experience of the team as well as the clinical scenario.…”
Section: Mechanical Ventilation During Ecmo Introductionmentioning
confidence: 99%
“…6 There are studies that encourage clinicians to consider an early tracheostomy even in situations where the risks associated with a tracheostomy, such as bleeding, are especially high. 7 Conversely, randomisation of patients into an early versus a late tracheostomy group has shown that if one waits with performing a tracheostomy (the 'late' group), the patient may end up not needing a tracheostomy at all. 8 However, there is neither a globally accepted consensus that determines optimal timing of tracheostomy, nor consensus on what is considered early vs a late tracheostomy.…”
Section: Introductionmentioning
confidence: 99%